2015
DOI: 10.1039/c5cc05239d
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed C–H activation of hydrazines leads to isoquinolones with tunable aggregation-induced emission properties

Abstract: Using an internally oxidizing directing group (DG) strategy, we report a Rh(III)-catalyzed synthesis of isoquinolones via C-H activation/annulation of benzoylhydrazines and alkynes. Tunable double cascade cyclization of benzoylhydrazines with two equivalents of alkynes led to tetracyclic amides. These N-heterocycles demonstrated adjustable AIE properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…The resulting products have large conjugated π-systems and the authors also investigated their photophysical properties. 338 …”
Section: Hydrazine and Hydrazone Derivatives As Dgsmentioning
confidence: 99%
“…The resulting products have large conjugated π-systems and the authors also investigated their photophysical properties. 338 …”
Section: Hydrazine and Hydrazone Derivatives As Dgsmentioning
confidence: 99%
“…Control experiments indicated that this transformation is a stepwise process and that isoquinolone is the key intermediate. Inspired by their works, Zhao, [23] Shi [24] and Dong [25] independently investigated Rh III ‐catalyzed cascade double C−H activation/annulation for the synthesis of the same type of tetracyclic products using different directing groups (Scheme 4).…”
Section: Rhodium Catalysismentioning
confidence: 99%
“…Both symmetrical and unsymmetrical alkynes were well tolerated under the optimized reaction conditions by giving corresponding products with high regioselectivity (Scheme 195). [201] In addition, authors have also demonstrated the one pot double cascade reaction to give structurally more complex polycyclic heterocycles. The scope of the reaction is diversified to have wide range of substituents on isoquinolone ring (Scheme 196).…”
Section: Rh-catalyzed Isoquinoline Synthesismentioning
confidence: 99%
“…Both symmetrical and unsymmetrical alkynes were well tolerated under the optimized reaction conditions by giving corresponding products with high regioselectivity (Scheme 195). [201] …”
Section: Synthesis Of Isoquinoline Derivativesmentioning
confidence: 99%